Curable composition and cured product

By using a specific combination of curable compositions, the problem of solder cracks caused by the underfill material during temperature cycle tests is solved, and the effects of high permeability and low thermal expansion are achieved, and the reliability of electronic components is improved.

CN112724596BActive Publication Date: 2025-04-18SUNSTAR GIKEN KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202011139786.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-10-28
Filing Date
2020-10-22
Publication Date
2025-04-18
Estimated Expiration
2040-10-22

AI Technical Summary

Technical Problem

Existing underfill materials may cause solder cracks in electronic component devices during temperature cycle tests, affecting reliability.

Method used

The curable composition including naphthalene type epoxy resin, glycidyl amine type epoxy resin, an amine-based curing agent with a melting point of 100°C or above, and an inorganic filler material is used to improve the permeability and thermal expansion inhibition performance of the cured product by optimizing the composition and process conditions.

Benefits of technology

High permeability before curing and low thermal expansion after curing are achieved, solder cracks in electronic component devices are reduced, and the reliability of electronic components is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002737865520000101
    Figure BDA0002737865520000101
  • Figure BDA0002737865520000111
    Figure BDA0002737865520000111
  • Figure BDA0002737865520000121
    Figure BDA0002737865520000121
Patent Text Reader

Abstract

The present invention relates to a curable composition and a cured product. The object of the present invention is to provide a curable composition that can achieve permeability before curing and suppression of thermal expansion after curing, and suppress poor reliability of electronic component devices. The curable composition of the present invention comprises a naphthalene-type epoxy resin (A1), a glycidylamine-type epoxy resin (A2), and an amine-based curing agent (B) having a melting point of 100° C. or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable composition, in particular a curable composition useful as an underfill material. Background Art

[0002] In the manufacture of electronic components, in order to fill the gap between the substrate and the electronic component and bond the substrate and the electronic component, an underfill material, which is a liquid composite resin, is generally used. The underfill material is required to have permeability to minute-sized gaps, and on the other hand, from the perspective of suppressing the occurrence of electronic component defects caused by deformation, the cured product of the underfill material is required to have a low thermal expansion coefficient.

[0003] Patent Document 1 discloses that an underfill material containing N,N-(diglycidyl)-toluidine can achieve both suppression of thermal expansion of a cured product and low viscosity during filling.

[0004] [Prior art literature]

[0005] [Patent Document]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 2019-11409 Summary of the invention

[0007] [Technical problem to be solved by the invention]

[0008] However, the inventors of the present application have found that, even if a material with a suppressed thermal expansion coefficient of a cured product is used as a bottom filling material, solder cracks may sometimes occur in electronic component devices during temperature cycle tests, resulting in poor reliability. It is presumed that this is because even if a material with a suppressed thermal expansion coefficient is used, undesirable internal stress may be generated in the electronic component device. The present invention is made in view of the above circumstances. That is, the main purpose of the present invention is to provide a curable composition that can achieve suppression of permeability before curing and thermal expansion after curing, and suppress poor reliability of electronic component devices.

[0009] [Solutions for solving technical problems]

[0010] The present invention is made in view of the above situation. An attempt is made to achieve the above purpose by treating it from a new direction, rather than responding to it by continuing the existing technology. As a result, it is found that the above main purpose can be achieved by using a specific composition focusing on the thermodynamic properties of the raw materials, the polarity of the raw materials, the shape of the raw materials, etc., thereby completing the present invention. One of the preferred embodiments of the present invention is as follows:

[0011] [Item 1] A curable composition comprising

[0012] Naphthalene type epoxy resin (A1),

[0013] Glycidylamine type epoxy resin (A2),

[0014] Amine curing agent (B) with a melting point of 100°C or above and

[0015] Inorganic filler material (C),

[0016] The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents.

[0017] [Item 2] The curable composition according to Item 1, wherein

[0018] The number of nitrogen atoms in the molecule of the amine curing agent (B) is 3 or more.

[0019] [Item 3] The curable composition according to Item 1 or 2, wherein

[0020] The nitrogen content of the amine curing agent (B) (14×the number of nitrogen atoms in the amine curing agent (B) molecule / the molecular weight of the amine curing agent (B)×100) is 20% by weight or more.

[0021] [Item 4] The curable composition according to any one of Items 1 to 3, wherein

[0022] The amine-based curing agent (B) is a curing agent containing a triazine skeleton.

[0023] [Item 5] The curable composition according to any one of Items 1 to 4, wherein

[0024] The amount of the naphthalene-type epoxy resin (A1) is 20% by weight or more based on the amount of organic matter in the composition.

[0025] The amount of the glycidylamine epoxy resin (A2) is 20% by weight or more based on the amount of organic matter in the composition.

[0026] [Item 6] The curable composition according to any one of Items 1 to 5, wherein

[0027] The glycidylamine epoxy resin (A2) is aromatic, and its monomer structure has only one nitrogen atom.

[0028] [Item 7] The curable composition according to any one of Items 1 to 6, wherein

[0029] The inorganic filler (C) includes spherical inorganic particles.

[0030] [Item 8] The curable composition according to Item 7, wherein

[0031] The spherical inorganic particles include

[0032] Spherical inorganic particles (Cs) with a center particle size in the range of 0.5 to 5 μm, and

[0033] Spherical inorganic particles (Cl) with a center particle size in the range of 5 to 20 μm,

[0034] The difference between the center particle diameter of the spherical inorganic particles (Cs) and the center particle diameter of the spherical inorganic particles (Cl) is at least 1 μm.

[0035] [Item 9] The curable composition according to Item 7, wherein

[0036] In the volume-based particle size distribution measurement of the spherical inorganic particles, in a particle abundance ratio diagram plotted with particle diameter as the horizontal axis and particle abundance ratio as the vertical axis, there are at least two peaks or shoulders in the particle diameter range of 0.5 to 20 μm.

[0037] [Item 10] A cured product of the curable composition according to any one of Items 1 to 9, wherein the linear expansion coefficient is 31 ppm or less.

[0038] [Item 11] A bottom filling material comprising

[0039] Naphthalene type epoxy resin (A1),

[0040] Glycidylamine type epoxy resin (A2),

[0041] Amine curing agent (B) having a melting point of 100°C or more and

[0042] Inorganic filler material (C),

[0043] The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents.

[0044] [Item 12] An electronic component device, wherein an electronic component and a substrate are connected using the underfill material according to Item 11 or a cured product thereof.

[0045] [Item 13] A method for manufacturing an electronic component device, comprising the step of filling the underfill material described in Item 11 into a gap between the electronic component and the substrate.

[0046] [Effects of the invention]

[0047] According to the present invention, a curable composition can be provided that can suppress permeability before curing and thermal expansion after curing. In addition, according to the present invention, a curable composition can be provided that can suppress reliability failure of an electronic component device. DETAILED DESCRIPTION

[0048] <Curable composition>

[0049] The curable composition in the present invention comprises a naphthalene type epoxy resin (A1), a glycidylamine type epoxy resin (A2), and an amine type curing agent (B) which is solid at room temperature.

[0050] [Characteristics of curable composition]

[0051] From the perspective of shortening the process, it is preferred that after the bottom filling material is applied to the substrate, the bottom filling material is infiltrated into the gap and cured at the same time. Therefore, it is required that the bottom filling material is also infiltrated during the heating in the curing furnace (e.g., 140°C, 20 minutes). From this perspective, it is advantageous to use a curable composition that does not fully cure below a certain temperature (e.g., 120°C) but cures quickly at a temperature above it.

[0052] The permeability of the curable composition (a prescribed amount of the curable composition is applied to the edge of two glass slides bonded together with a spacer of 100 μm, and the penetration distance of the curable composition after the temperature is raised from 25° C. to 140° C. over 10 minutes. Details of the measurement method are described in the examples.) can be 18 mm or more, 23 mm or more, 28 mm or more, 33 mm or more, or 38 mm or more, preferably 21 mm or more, more preferably 26 mm or more, and even more preferably 31 mm or more.

[0053] The viscosity increase of the curable composition after storage at 40° C. for 96 hours may be 1.4 times or less, 1.35 times or less, 1.3 times or less, 1.25 times or less, 1.2 times or less, 1.15 times or less, 1.1 times or less, or 1.05 times or less, preferably 1.23 times or less, and more preferably 1.13 times or less, based on the viscosity increase before storage at 40° C. within the above range. By setting the viscosity increase after storage at 40° C. for 96 hours to be within the above range, productivity is improved.

[0054] The reaction rate of the curable composition after heating at 150° C. for 3 minutes may be 91% or more, 93% or more, 95% or more, 97% or more, or 99% or more, preferably 92.5% or more, and more preferably 97.5% or more. When the reaction rate of the curable composition after heating at 150° C. for 3 minutes is within the above range, workability is improved.

[0055] [Epoxy resin]

[0056] The curable composition of the present invention comprises an epoxy resin. In the present specification, the so-called "epoxy resin" refers to an epoxy resin in a state before reacting with a curing agent. The epoxy resin can be liquid or solid at room temperature, preferably liquid at room temperature. The epoxy resin can be a monomeric epoxy resin, a prepolymer epoxy resin, or a mixture of a monomeric epoxy resin and a prepolymer resin (for example, a degree of polymerization of 2 to 5 or 2 to 3).

[0057] The curable composition in the present invention contains a naphthalene type epoxy resin (A1) and a glycidylamine type epoxy resin (A2).

[0058] (Naphthalene type epoxy resin (A1))

[0059] The curable composition of the present invention comprises a naphthalene-type epoxy resin (A1). "Naphthalene-type epoxy resin" is an epoxy resin having a naphthalene skeleton in the molecule. The naphthalene-type epoxy resin (A1) may contain other groups such as aliphatic groups and aromatic groups. As the epoxy-containing group, a glycidyl group (e.g., a glycidyl ether group or a glycidyl amino group) may be used. The naphthalene-type epoxy resin (A1) may not have a glycidyl amino group.

[0060] The linear expansion coefficient of the cured product obtained by using epoxy resin (A1) is easily reduced. In addition, by using epoxy resin (A1), even if the amount of filler (such as silica) in the curable composition increases, it is easy to maintain the low linear expansion coefficient and insulation of the cured product. It is presumed that this is because: since the occupied volume of epoxy resin (A1) is small, it is possible to prevent the filler particles from colliding with each other in the epoxy resin.

[0061] The number of nitrogen atoms in the monomer structure of the epoxy resin (A1) is 0 to 2, preferably 0 to 1, and more preferably 0. By reducing the number of nitrogen atoms in the epoxy resin (A1), the insulation properties of the cured product can be improved while maintaining heat resistance.

[0062] The epoxy resin (A1) may be a monomer type (polymerization degree 1) or a prepolymer type (e.g., polymerization degree 2 to 5 or 2 to 3). The epoxy resin (A1) preferably includes a monomer type. The average polymerization degree of the epoxy resin (A1) may be 1 to 2.5, preferably 1 to 1.5. By lowering the polymerization degree of the epoxy resin, it is possible to easily achieve low viscosity and excellent workability.

[0063] The number of naphthyl groups in the monomer type of the epoxy resin (A1) may be 1, 2 or 3, and preferably 1 or 2.

[0064] The number of epoxy groups in the monomer type of the epoxy resin (A1) may be 1 to 6, 2 to 5, 2 to 4, 2 to 3 or 2 (diepyl group), and is preferably 2 to 3 or 2.

[0065] The weight average molecular weight of the epoxy resin (A1) may be 100 to 1200, 150 to 900, or 200 to 600, and is preferably 180 to 750. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) in terms of polystyrene.

[0066] The epoxy equivalent of the epoxy resin (A1) may be 50 to 500, 60 to 400, or 100 to 300, and preferably 80 to 350. As a method for determining the epoxy equivalent of the epoxy resin, for example, JIS K7236:2001 can be referred to.

[0067] Examples of the epoxy resin (A1) include monoepoxynaphthalenes such as 1-glycidyloxynaphthalene and 2-glycidyloxynaphthalene; diepoxynaphthalenes such as 1,2-diglycidyloxynaphthalene, 1,5-diglycidyloxynaphthalene, 1,6-diglycidyloxynaphthalene (e.g., EPICLON HP-4032D manufactured by DIC Corporation), 1,7-diglycidyloxynaphthalene, 2,7-diglycidyloxynaphthalene; triglycidyloxynaphthalene and 1,2,5,6-tetraglycidyloxynaphthalene; a binaphthyl epoxy resin having a structure in which two naphthyl groups are bonded via an organic group (e.g., EPICLON HP-4700 manufactured by DIC Corporation); and prepolymers thereof, and modified products thereof. These may be used alone or in combination of two or more.

[0068] (Glycidylamine type epoxy resin (A2))

[0069] The curable composition of the present invention contains a glycidylamine epoxy resin (A2). A "glycidylamine epoxy resin" is an epoxy resin having a glycidylamino group in the molecule. By using the epoxy resin (A1) and the epoxy resin (A2) together, permeability and heat resistance become good.

[0070] The epoxy resin (A2) preferably has an aromatic group. For example, the epoxy resin (A2) may have an aromatic hydrocarbon skeleton such as a benzene skeleton, a biphenyl skeleton, a naphthalene skeleton, an anthracene skeleton, and a phenanthrene skeleton; and / or an aromatic hydrocarbon skeleton containing a nitrogen group such as pyridine and triazine. By making the epoxy resin (A2) have an aromatic group, heat resistance can be improved. In addition, by making the epoxy resin (A2) have an aromatic group, hygroscopicity can be reduced and insulation can be improved.

[0071] The monomer structure of the epoxy resin (A2) has at least one nitrogen atom derived from a glycidylamino group, and the number of nitrogen atoms other than these is 0 to 2, preferably 0 to 1, and more preferably 0. That is, the monomer structure of the epoxy resin (A2) preferably has only one nitrogen atom. By reducing the number of nitrogen atoms in the epoxy resin (A2), it is possible to reduce hygroscopicity and improve the insulation properties of the cured product while maintaining heat resistance.

[0072] The nitrogen content of the epoxy resin (A2) (14×the number of nitrogen atoms in the monomer structure molecule of the epoxy resin (A2) / the molecular weight of the monomer structure of the epoxy resin (A2)×100) can be 30% or less, 20% or less, 10% or less, or 7.5% or less, preferably 15% or less, and more preferably 6% or less.

[0073] The epoxy resin (A2) may be a monomer type (polymerization degree 1) or a prepolymer type (for example, a polymerization degree 2 to 5 or 2 to 3). The epoxy resin (A2) preferably includes a monomer type. The average polymerization degree of the epoxy resin (A2) may be 1 to 2.5, preferably 1 to 1.5. By lowering the polymerization degree of the epoxy resin, it is possible to easily achieve low viscosity and excellent workability.

[0074] The number of glycidylamino groups in the monomeric form of the epoxy resin (A2) may be 1, 2 or 3, and preferably 1 or 2.

[0075] From the viewpoint of heat resistance, the number of epoxy groups in the monomer structure of the epoxy resin (A2) may be 1 to 7, 2 to 5, 2 to 4 or 2 to 3, preferably 3 to 4, particularly preferably 3 (triepoxy group). The epoxy groups other than the epoxy groups contained in the glycidylamino group may be epoxy groups contained in the glycidylether group.

[0076] The weight average molecular weight of the monomer structure of the epoxy resin (A2) may be 100 to 1200, 150 to 900, or 200 to 600, and preferably 180 to 750. The weight average molecular weight may be a value measured by gel permeation chromatography (GPC) in terms of polystyrene.

[0077] The epoxy equivalent of the epoxy resin (A2) may be 50 to 450, 60 to 350, or 100 to 250, and preferably 80 to 300. As a method for determining the epoxy equivalent of the epoxy resin, for example, JIS K7236:2001 can be referred to.

[0078] Examples of epoxy resins (A2) include aromatic types such as N,N-diglycidyl-4-(glycidyloxy)aniline, 4,4'-methylenebis[N,N-bis(oxiranylmethyl)aniline](4,4'-Methylenebis(N,N-bis(oxiranylmethyl)aniline)), triglycidyl-o-aminophenol, triglycidyl-p-aminophenol; aliphatic types such as 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane; isocyanurate types such as monoglycidyl isocyanurate, diglycidyl isocyanurate, and triglycidyl isocyanurate; hydantoin types such as diglycidyl hydantoin; and prepolymers thereof, and modified products thereof. These may be used alone or in combination of two or more. The epoxy resin (A2) preferably has a diglycidylamino group.

[0079] (Other epoxy resins)

[0080] The curable composition preferably contains an epoxy resin other than the naphthalene-type epoxy resin (A1) and the glycidylamine-type epoxy resin (A2).

[0081] As examples of other epoxy resins, bisphenol-type epoxy resins such as bisphenol A type, bisphenol F type, bisphenol E (AD) type and bisphenol S type can be cited; phenol Novolac type epoxy resins, cresol Novolac type epoxy resins and Novolac type epoxy resins such as bisphenol A; aromatic epoxy resins such as biphenyl type, triphenylmethane type, dicyclopentadiene type, fluorene type and anthracene type; alicyclic epoxy resins such as norbornene type epoxy resin and adamantane type epoxy resin; aliphatic chain epoxy resin; phosphorus-containing epoxy resin; and alkylphenol type epoxy resins, and their modified products. From the viewpoint of heat resistance, aromatic epoxy resins can be contained as other epoxy resins. In addition, from the viewpoint of heat resistance, aliphatic epoxy resins may not be contained as other epoxy resins. As a preferred example of other epoxy resins, bisphenol epoxy resins can be cited. The epoxy resin may not contain active hydrogen-containing groups and active hydrogen-reactive groups other than epoxy groups. These may be used alone or in combination of two or more. The other epoxy resin may not contain an aliphatic epoxy resin.

[0082] The number of nitrogen atoms in the monomer structure of the other epoxy resin is 0 to 2, preferably 0 to 1, and more preferably 0.

[0083] [Curing agent]

[0084] (Amine curing agent (B))

[0085] The curable composition preferably contains an amine curing agent (B) which is solid at room temperature. In the present invention, the amine curing agent refers to a substance having an amino group in the molecule which has the function of enabling or accelerating the curing reaction when added to a thermosetting resin. Here, the so-called "amino group" includes an amino group contained in an imidazole skeleton or an imidazoline skeleton, and is a group considered to be an amino group by a person skilled in the art. In addition, the "curing agent" in this specification may be a broad concept that also includes a curing accelerator.

[0086] When the curable composition is used as an underfill material, it is important to select a curing agent that can impart to the curable composition a curing property that does not fully cure below a certain temperature, but can rapidly cure at a temperature above the certain temperature. As such a curing agent (B), a curing agent having a high melting point and multiple nitrogen atoms in the molecule is preferred. It is inferred that the presence of nitrogen atoms improves the reaction activity of the curing agent (B) with the epoxy resin (A1) and the epoxy resin (A2), and contributes to excellent curability.

[0087] From the viewpoint of curability when used as an underfill material, the melting point of the amine curing agent (B) may be 50° C. or higher, 100° C. or higher, 120° C. or higher, 150° C. or higher, 175° C. or higher, or 200° C. or higher, preferably 100° C. or higher, more preferably 150° C. or higher, more preferably 180° C. or higher, further preferably 210° C. or higher, and further preferably 240° C. or higher. In addition, the melting point of the amine curing agent (B) may be 400° C. or lower, 350° C. or lower, 300° C. or lower, or 280° C. or lower.

[0088] From the viewpoint of curability when used as an underfill material, the number of nitrogen atoms in the molecule of the amine curing agent (B) may be 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or 8 or more, preferably 3 or more, and more preferably 5 or more. The number of nitrogen atoms in the molecule of the amine curing agent (B) may be 12 or less, 10 or less, or 8 or less.

[0089] From the viewpoint of curability when used as an underfill material, the nitrogen content of the amine curing agent (B) (14×the number of nitrogen atoms in the amine curing agent (B) molecule / the molecular weight of the amine curing agent (B)×100) may be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, or 42% by weight or more, for example, 18% by weight or more, preferably 28% by weight or more, and particularly preferably 38% by weight or more. In addition, the nitrogen content of the amine curing agent (B) may be 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less.

[0090] The amine curing agent (B) may be, for example, an aliphatic monoamine, an aliphatic polyamine, an aromatic monoamine or an aromatic polyamine. The amine curing agent (B) may not be an amine adduct formed with the epoxy resin. From the viewpoint of curability, the amine curing agent (B) may not have a hydroxyl group.

[0091] The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents. The amine curing agent (B) may be used alone or in combination of two or more.

[0092] "Imidazole curing agent" is a curing agent having an imidazole skeleton in the molecule. Examples of imidazole curing agents include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-phenylimidazole, 1-aminoethyl-2-methylimidazole, 1-(2-hydroxy-3-phenoxypropyl)-2-methylimidazole, 1-(2-hydroxy-3-phenoxypropyl)-2-ethyl-4-methylimidazole, 1-(2-hydroxy-3-butoxypropyl)-2-methylimidazole, 1-(2-hydroxy-3-butoxypropyl)-2-ethyl-4-methylimidazole and 1-cyanoethyl-2-undecylimidazole trimellitate, and modified products thereof. These may be used alone or in combination of two or more. From the viewpoint of curability, the imidazole curing agent may not have a hydroxyl group.

[0093] An "imidazoline curing agent" is a curing agent having an imidazoline skeleton in the molecule. Examples of imidazoline curing agents include 1-(2-hydroxy-3-phenoxypropyl)-2-phenylimidazoline, 1-(2-hydroxy-3-butoxypropyl)-2-methylimidazoline, 2-methylimidazoline, 2,4-dimethylimidazoline, 2-ethylimidazoline, 2-ethyl-4-methylimidazoline, 2-benzylimidazolidine, 2-phenylimidazoline, 2-(o-tolyl)-imidazoline, tetramethylene-bis-imidazoline, 1,1,3-trimethyl-1,4-tetramethylimidazoline, Methylene-bis-imidazoline, 1,3,3-trimethyl-1,4-tetramethylene-bis-imidazoline, 1,1,3-trimethyl-1,4-tetramethylene-bis-4-methylimidazoline, 1,3,3-trimethyl-1,4-tetramethylene-bis-4-methylimidazoline, 1,2-phenylene-bis-imidazoline, 1,3-phenylene-bis-imidazoline, 1,4-phenylene-bis-imidazoline and 1,4-phenylene-bis-4-methylimidazoline, and modified products thereof. These may be used alone or in combination of two or more. From the viewpoint of curability, the imidazoline curing agent may not have a hydroxyl group.

[0094] The amine curing agent (B) may be at least one selected from the group consisting of triazine skeleton-containing amine curing agents containing a triazine skeleton (particularly 1,3,5-triazine skeleton) in the molecule, that is, triazine skeleton-containing imidazole curing agents and triazine skeleton-containing imidazoline curing agents.

[0095] By making the amine curing agent (B) contain a triazine skeleton, good permeability can be obtained and good reaction promotion can be achieved. The reason is not yet clear, but it is presumed that the melting point of the curing agent is moderately increased by containing a triazine skeleton, and the presence of three ring nitrogen atoms achieves a moderate interaction with other components.

[0096] The amine curing agent containing a triazine skeleton may have at least one (e.g., one, two, or three) amino group directly bonded to the triazine skeleton, preferably two. From the viewpoint of curability, the amine curing agent containing a triazine skeleton may not have a hydroxyl group directly bonded to the triazine skeleton. The amine curing agent containing a triazine skeleton may be a compound represented by the following general formula (1).

[0097]

[0098] (In formula (1), R 1 , R 2 and R 3 are each independently a hydrogen atom or a monovalent organic group having 1 to 25 carbon atoms, R 1 , R 2 and R 3 At least one of them is a group containing an imidazole skeleton or an imidazoline skeleton.

[0099] R 1 , R 2 and R 3 The monovalent organic group in R can be an aliphatic group or an aromatic group. 1 , R 2 and R 3 At least one (preferably one) of the groups is a group containing an imidazole skeleton or an imidazoline skeleton. 1 , R 2 and R 3 At least one, preferably two, of the R are amino groups (alkylamino groups, -NH2 groups, preferably -NH2 groups). 1 , R 2 and R 3 The molecular weight of R may be 10 to 750, for example (particularly in the case of a group containing an imidazole skeleton or an imidazoline skeleton) 200 to 400. 1 , R 2 and R 3 The number of carbon atoms may be 0-20, for example 1-15.

[0100] R 2 and R 3 In the case of amino group, R 1 It may be a group containing an imidazole skeleton or an imidazoline skeleton, and is preferably a group containing an imidazole group. 1 It may or may not have a hydroxyl group.

[0101] The triazine skeleton-containing amine-based curing agent may be a compound represented by the following general formula (2).

[0102]

[0103] (In formula (2), R 4 is an organic group having 3 to 25 carbon atoms and containing an imidazole skeleton or an imidazoline skeleton, R 5 , R 6 , R 7 and R 8 Each is independently a hydrogen atom or a monovalent organic group having 1 to 25 carbon atoms.

[0104] R 4 The imidazole skeleton or imidazoline skeleton in the triazine skeleton may be bonded to the triazine skeleton via a spacer group (for example, an aliphatic hydrocarbon group or a nitrogen-containing aliphatic hydrocarbon group) or directly bonded to the imidazole skeleton or imidazoline skeleton. 4 The number of carbon atoms in can be 3-20, for example 3-15.

[0105] R 5 , R 6 , R 7 and R 8 The organic groups in R are each independent and may be an aliphatic group or an aromatic group, preferably an aliphatic group (such as an aliphatic hydrocarbon group), such as an alkyl group, an alkenyl group, an aryl group or a hydroxyalkyl group, more preferably an alkyl group or an alkenyl group. 5 , R 6 , R 7 and R 8 The number of carbon atoms of the organic group in R may be 1 to 20, for example, 1 to 15. 5 , R 6 , R 7 and R 8 At least one (for example, one, two, or three) of them may be a hydrogen atom, and all of them may be hydrogen atoms.

[0106] The imidazole curing agent containing a triazine skeleton may be a compound represented by the following general formula (3).

[0107]

[0108] (In formula (3), R 9, R 10 and R 11 Each is independently a hydrogen atom or an organic group having 1 to 25 carbon atoms, and L is a direct bond or an organic group having 1 to 25 carbon atoms.)

[0109] R 9 , R 10 and R 11 The organic groups in R are each independent and may be an aliphatic group or an aromatic group, preferably an aliphatic group (such as an aliphatic hydrocarbon group), such as an alkyl group, an alkenyl group, an aryl group or a hydroxyalkyl group, more preferably an alkyl group or an alkenyl group. 9 , R 10 and R 11 The number of carbon atoms of the organic group in R may be 1 to 20, for example, 1 to 15. 9 , R 10 and R 11 At least one (e.g., one or two, especially R 9 and R 10 One or both of them may be hydrogen atoms, or all of them may be hydrogen atoms.

[0110] L 1 The organic group in L may be a divalent aliphatic group or a divalent aromatic group, and is preferably an aliphatic group (eg, an aliphatic hydrocarbon group, an oxygen-containing aliphatic hydrocarbon group or a nitrogen-containing aliphatic hydrocarbon group). 1 The organic group in L may have one or more nitrogen atoms or oxygen atoms, or may not have one or more nitrogen atoms or oxygen atoms. 1 The organic group in may have 1 to 20 carbon atoms, for example, 1 to 15 carbon atoms.

[0111] The imidazoline curing agent containing a triazine skeleton may be a compound represented by the following general formula (4).

[0112]

[0113] (In formula (4), R 12 , R 13 and R 14 Each of them is independently a hydrogen atom or an organic group having 1 to 25 carbon atoms, L 2 It is a direct bond or an organic group having 1 to 25 carbon atoms. )

[0114] R 12 , R 13 and R 14 The organic groups in R are each independent and may be an aliphatic group or an aromatic group, preferably an aliphatic group (such as an aliphatic hydrocarbon group), such as an alkyl group, an alkenyl group, an aryl group or a hydroxyalkyl group, more preferably an alkyl group or an alkenyl group. 12 , R13 and R 14 The number of carbon atoms of the organic group in R may be 1 to 20, for example, 1 to 15. 12 , R 13 and R 14 At least one (e.g., one or two, especially R 12 and R 13 One or both of them may be hydrogen atoms, or all of them may be hydrogen atoms.

[0115] L 2 The organic group in L may be a divalent aliphatic group or a divalent aromatic group, and is preferably an aliphatic group (eg, an aliphatic hydrocarbon group, an oxygen-containing aliphatic hydrocarbon group or a nitrogen-containing aliphatic hydrocarbon group). 2 The organic group in L may have one or more nitrogen atoms or oxygen atoms, or may not have one or more nitrogen atoms or oxygen atoms. 2 The organic group in may have 1 to 20 carbon atoms, for example, 1 to 15 carbon atoms.

[0116] As the triazine skeleton-containing curing agent, a commercial product can be used, and it can be produced by a method known to those skilled in the art. For example, reference can be made to International Publication No. 2014 / 142035, Japanese Patent Application Laid-Open No. 2015-140394, and Japanese Patent Application Laid-Open No. 2019-6972.

[0117] Examples of the curing agent containing a triazine skeleton include 1-(4,6-diamino-s-triazine-2-yl)butyl-2-undecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-undecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-heptadecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-ethyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-phenylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-phenylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-phenyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-phenyl-4,5-dihydroxymethylimidazole; 1-(4,6-diamino-s-triazine-2-yl)propyl-2-phenyl-4-hydroxymethyl-5-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-undecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-heptadecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-ethyl-4-methylimidazole ; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-phenylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-phenyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-phenyl-4,5-dihydroxymethylimidazole; 1-(4,6-diamino-s-triazine-2-yl)butyl-2-phenyl-4-hydroxymethyl-5-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-undecylimidazole; 1-(4,6-diamino-s-triazine-2 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-heptadecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-ethyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-phenylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-phenyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-phenyl-4,5-dihydroxymethylimidazole; 1-(4,6-diamino-s-triazine-2-yl)pentyl-2-phenyl-4-hydroxymethyl-5-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)hexylimidazole; 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-methylimidazole;1-(4,6-diamino-s-triazine-2-yl)hexyl-2-undecyl imidazole; 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-heptadecylimidazole; 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-ethyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-phenylimidazole; 1-(4,6-diamino-s-triazine-2 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-phenyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-phenyl-4,5-dihydroxymethylimidazole; 1-(4,6-diamino-s-triazine-2-yl)hexyl-2-phenyl-4-hydroxymethyl-5-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)heptylimidazole; 1-(4,6-diamino-s-triazine-2-yl) Heptyl-2-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl) heptyl-2-undecylimidazole; 1-(4,6-diamino-s-triazine-2-yl) heptyl-2-heptadecylimidazole; 1-(4,6-diamino-s-triazine-2-yl) heptyl-2-ethyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl) heptyl-2-phenylimidazole; 1-(4,6 -(4,6-diamino-s-triazine-2-yl)heptyl-2-phenyl-4-methylimidazole; 1-(4,6-diamino-s-triazine-2-yl)heptyl-2-phenyl-4,5-dihydroxymethylimidazole; 1-(4,6-diamino-s-triazine-2-yl)heptyl-2-phenyl-4-hydroxymethyl-5-methylimidazole; and compounds obtained by replacing their imidazole skeletons with imidazoline skeletons, and their modified products. Specific examples of products include 2MZ-A, 2MZA-PW, C11Z-A and 2E4MZ-A manufactured by Shikoku Chemical Co., Ltd. They can be used alone or in combination of two or more. From the perspective of curability, the imidazoline curing agent does not have to have a hydroxyl group. ;

[0118] When the curing agent (B) is in a solid state, the curing agent (B) may be ground to a predetermined center particle size. Examples of the center particle size of the curing agent (B) are 10 μm or less, 5 μm or less, 2.5 μm or less, and 1.5 μm or less. The grinding may be performed using an air flow grinder such as a jet mill; a ball mill such as a vibrating ball mill, a continuous rotary ball mill, and a batch ball mill; a ball mill such as a wet ball mill and a planetary ball mill; or a grinder such as a roll crusher.

[0119] (Other curing agents)

[0120] The curable composition of the present invention may contain other curing agents other than the curing agent (B). Examples of other curing agents include amine compounds (e.g., aliphatic amines, alicyclic and heterocyclic amines, aromatic amines and modified amines), imidazole compounds, imidazoline compounds, amide compounds, ester compounds, phenolic compounds, alcohol compounds, thiol compounds, ether compounds, thioether compounds, urea compounds, thiourea compounds, Lewis acid compounds, phosphorus compounds, anhydride compounds, onium salt compounds (or cationic polymerization initiators) and active silicon compound-aluminum complexes. From the perspective of insulation, the curable composition of the present invention may not use an anhydride curing agent. The curable composition may not contain a curing agent that is liquid at room temperature.

[0121] [Inorganic filler (C)]

[0122] About the curable composition

[0123] The curable composition of the present invention contains an inorganic filler (C). The inorganic filler (C) may be an inorganic filler generally used in a curable composition, and is preferably at least one selected from the group consisting of silica particles and alumina particles.

[0124] (Spherical inorganic particles)

[0125] The curable composition of the present invention preferably contains spherical inorganic particles as a filler. The spherical inorganic particles are preferably at least one selected from the group consisting of silica particles and alumina particles. The spherical inorganic particles can be treated with various surface treatment agents (e.g., silane coupling agents). In this specification, the so-called spherical is not limited to a spherical shape, an elliptical spherical shape, etc., as long as the spherical shape is considered to be spherical by a person skilled in the art. For example, particles with some convex and concave surfaces can also be spherical particles.

[0126] The spherical inorganic particles may include a plurality of (for example, 2, 3 or 4) particles having different particle size distributions. The spherical inorganic particles may include a plurality of (for example, 2, 3 or 4) particles having different particle distributions with a central particle diameter in the range of 0.5 to 20 μm. The spherical inorganic particles may include spherical inorganic particles (Cs) having a small central particle diameter and spherical inorganic particles (Cl) having a large central particle diameter. The central particle diameter of the spherical inorganic particles (Cs) may be 0.5 to 5 μm, 0.5 to 4.5 μm or 0.5 to 3 μm, preferably 0.5 to 4 μm. The central particle diameter of the spherical inorganic particles (Cl) having a large central particle diameter may be 5 to 20 μm, 7 to 20 μm or 9 to 20 μm, preferably 7.5 to 20 μm. The difference between the center particle diameter of the spherical inorganic particles (Cs) and the spherical inorganic particles (Cl) can be at least 1 μm, at least 2.5 μm, at least 5 μm, or at least 10 μm. The center particle diameter and particle size distribution can be measured, for example, using a laser diffraction / scattering particle distribution measuring device. Specifically, the method described in the embodiment can be used to measure. It should be noted that "center particle diameter" represents the value of d50 in the volume-based particle size distribution measurement.

[0127] In the volume-based particle size distribution measurement of spherical inorganic particles, in the particle existence ratio diagram obtained by plotting the particle diameter as the horizontal axis and the particle existence ratio as the vertical axis, it is preferred to have multiple (for example, 2, 3 or 4) peaks or shoulders in the range of particle diameter 0.5 to 20 μm (here, shoulder refers to: when there are two or more peaks and one peak is significantly smaller than the other peaks, when they overlap, the peak appears as a shoulder on the large peak). The particle diameter difference between any two peaks of the multiple peaks can be at least 1 μm, at least 2.5 μm, at least 5 μm, or at least 10 μm.

[0128] (Other inorganic fillers)

[0129] Examples of other inorganic fillers include glass, calcium carbonate, fatty acid-treated calcium carbonate, pyrogenic silica, precipitated silica, carbon black, talc, mica, clay, glass beads, white sand stacking balls, glass balls, silica balls, plastic balls, glass fibers, metal fibers and other inorganic fibers, aluminum borate, silicon carbide, silicon nitride, potassium titanate, graphite, needle-shaped crystalline calcium carbonate, magnesium borate, titanium diboride, chrysotile asbestos, wollastonite and other needle-shaped crystalline fillers, etc., in addition to the above-mentioned spherical inorganic particles.

[0130] In order to enhance the bonding strength between the resin and the inorganic filler, the inorganic filler can be pre-surface treated with a coupling agent such as a silane coupling agent or a titanate coupling agent. Examples of such coupling agents include epoxysilanes such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; aminosilanes such as N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, a reaction product of imidazole and γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; and silane coupling agents such as mercaptosilanes such as γ-mercaptosilane and γ-episulfidoxypropyltrimethoxysilane.

[0131] [Other additives]

[0132] The curable composition of the present invention may contain other additives. Examples of other additives include colorants such as carbon black, organic dyes and organic pigments; organic fillers such as organic particles and organic fibers; silicone additives such as vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, mercaptosilane, epoxysilane and silicone oil (such as amino-modified silicone oil and epoxy-modified silicone oil); epoxy compounds such as glycidyl ether having a polyoxyalkylene skeleton; anti-aging agents / antioxidants such as hindered phenols, thiols, sulfides, disulfide carboxylates, thioureas, thiophosphates and thioaldehydes; ultraviolet absorbers and light stabilizers such as benzotriazoles and hindered amines; thixotropic agents such as colloidal silica, organic bentonite, fatty acid amides and hydrogenated castor oil; modifiers such as thermoplastic elastomers, NR (natural rubber), NBR (acrylonitrile-butadiene rubber), acrylic rubber, urethane rubber, silicone rubber, etc. For example, a silane coupling agent such as epoxysilane may be added in combination with silicone oil.

[0133] [Composition of curable composition]

[0134] (Total amount of epoxy resin)

[0135] The total amount of the epoxy resin may be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more, preferably 18% by weight or more, and more preferably 28% by weight or more, relative to the composition. In addition, the total amount of the epoxy resin may be 60% by weight or less, 55% by weight or less, 50% by weight or less, 45% by weight or less, 40% by weight or less, or 35% by weight or less, preferably 58% by weight or less, and more preferably 48% by weight or less, relative to the composition.

[0136] (Amount of naphthalene type epoxy resin (A1))

[0137] The amount of epoxy resin (A1) can be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more or 35% by weight or more relative to the amount of organic matter in the composition, preferably 17% by weight or more, more preferably 28% by weight or more, and more preferably 33% by weight or more. In addition, the amount of epoxy resin (A1) can be 75% by weight or less, 65% by weight or less, 55% by weight or less, 45% by weight or less or 40% by weight or less relative to the amount of organic matter in the composition, preferably 60% by weight or less, more preferably 50% by weight or less, and more preferably 39% by weight or less. It should be noted that in this specification, the so-called "amount of organic matter in the composition" can be the amount other than the inorganic particles in the composition, and can also be interpreted as the total amount of epoxy resin in the composition.

[0138] (Weight of naphthalene skeleton in epoxy resin (A1))

[0139] The weight of the naphthalene skeleton of the epoxy resin (A1) may be 1% by weight or more, 2.5% by weight or more, 4.5% by weight or more, 6% by weight or more, or 7.5% by weight or more, preferably 3% by weight or more, more preferably 5.5% by weight or more, and further preferably 6.5% by weight or more, relative to the composition. In addition, the weight of the naphthalene skeleton of the epoxy resin (A1) may be 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, or 10% by weight or less, preferably 26% by weight or less, more preferably 16% by weight or less, and further preferably 11% by weight or less, relative to the composition.

[0140] (Amount of glycidylamine type epoxy resin (A2))

[0141] The amount of the epoxy resin (A2) can be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more relative to the amount of organic matter in the composition, preferably 21% by weight or more, more preferably 28% by weight or more, and further preferably 35% by weight or more. In addition, the amount of the epoxy resin (A2) can be 75% by weight or less, 65% by weight or less, 55% by weight or less, 45% by weight or less, or 40% by weight or less relative to the amount of organic matter in the composition, preferably 65% ​​by weight or less, more preferably 45% by weight or less, and further preferably 39% by weight or less.

[0142] (Amount of other epoxy resins)

[0143] The amount of other epoxy resins relative to the amount of organic matter in the composition may be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, or 35% by weight or more, preferably 21% by weight or more, more preferably 28% by weight or more, and even more preferably 35% by weight or more. In addition, the amount of other epoxy resins relative to the amount of organic matter in the composition may be 75% by weight or less, 65% by weight or less, 55% by weight or less, 45% by weight or less, 40% by weight or less, 30% by weight or less, 25% by weight or less, or 15% by weight or less, preferably 65% ​​by weight or less, more preferably 45% by weight or less, and even more preferably 39% by weight or less.

[0144] (Weight of nitrogen atoms)

[0145] The weight of nitrogen atoms in the composition may be 0.5% by weight or more, 0.8% by weight or more, or 1.0% by weight or more, relative to the composition. In addition, the weight of nitrogen atoms in the composition may be 15% by weight or less, 12% by weight or less, 9% by weight or less, 6% by weight or less, 3% by weight or less, or 1.5% by weight or less, preferably 7.5% by weight or less, and more preferably 2.5% by weight or less, relative to the composition.

[0146] (Total amount of inorganic filler (C))

[0147] The total amount of inorganic filler (C) can be 40% by weight or more, 45% by weight or more, 50% by weight or more, 55% by weight or more, 60% by weight or more, or 65% by weight or more, preferably 43% by weight or more, and more preferably 53% by weight or more. In addition, the total amount of inorganic filler (C) can be 80% by weight or less, 75% by weight or less, 70% by weight or less, 65% by weight or less, or 60% by weight or less, preferably 70% by weight or more, preferably 66% by weight or less, and more preferably 63% by weight or less, relative to the composition. By making the amount of inorganic filler in the above range, the permeability and / or linear expansion coefficient of the curable composition can be improved.

[0148] The total amount of the inorganic filler (C) relative to the composition can be 30% by volume or more, 33% by volume or more, 36% by volume or more, 39% by volume or more, 41% by volume or more, or 43% by volume or more, preferably 35% by volume or more, and more preferably 40% by volume or more. In addition, the total amount of the inorganic filler (C) relative to the composition can be 80% by volume or less, 65% by volume or less, 50% by volume or less, 45% by volume or less, 40% by volume or less, or 35% by volume or less, preferably 76% by volume or less, and more preferably 66% by volume or less.

[0149] (Amount of spherical inorganic particles)

[0150] The amount of the spherical inorganic particles relative to the total amount of the inorganic filler (C) can be 70% by weight or more, 75% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more, preferably 85% by weight or more, and more preferably 95% by weight or more. In addition, the amount of the spherical inorganic particles relative to the total amount of the filler can be 100% by weight or less, 97% by weight or less, 93% by weight or less, 90% by weight or less, 85% by weight or less, or 80% by weight or less.

[0151] (Amount of spherical inorganic particles (Cl))

[0152] The amount of spherical inorganic particles (Cl) can be more than 30 weight %, more than 30 weight %, more than 40 weight %, more than 50 weight %, preferably more than 42 weight %, more preferably more than 45 weight %. In addition, the total amount of inorganic filler (Cl) can be less than 65 weight %, less than 60 weight %, less than 55 weight %, less than 50 weight %, less than 48 weight % or less than 45 weight %, preferably less than 54 weight %, more preferably less than 50 weight %. By making the amount of inorganic filler in the above range, the permeability and / or linear expansion coefficient of curable composition can be improved.

[0153] (Amount of spherical inorganic particles (Cs))

[0154] The amount of the spherical inorganic particles (Cs) can be 3% by weight or more, 5% by weight or more, 7.5% by weight or more, 15% by weight or more, or 17.5% by weight or more, preferably 4.5% by weight or more, and more preferably 8% by weight or more, relative to the composition. In addition, the total amount of the inorganic filler (C) can be 40% by weight or less, 25% by weight or less, or 15% by weight or less, preferably 18% by weight or less, and more preferably 13% by weight or less, relative to the composition. By making the amount of the inorganic filler in the above range, the permeability of the curable composition can be improved.

[0155] (Amount of curing agent)

[0156] The amount of the curing agent can be 0.01% by weight or more, 0.2% by weight or more, 0.4% by weight or more, 0.6% by weight or more, 0.8% by weight or more, or 1.0% by weight or more, preferably 0.3% by weight or more, and more preferably 0.7% by weight or more, relative to the composition. In addition, the total amount of the curing agent can be 50% by weight or less, 35% by weight or less, 20% by weight or less, 15% by weight or less, 5% by weight or less, 4.5% by weight or less, 3.5% by weight or less, 3% by weight or less, 2.5% by weight or less, or 2% by weight or less, preferably 3.6% by weight or less, and more preferably 2.2% by weight or less.

[0157] The mixing ratio of the epoxy resin to the curing agent may be set to a ratio of epoxy resin to curing agent (weight of epoxy resin / weight of curing agent) of less than 100, less than 50, or less than 25 from the viewpoint of curing speed.

[0158] (Amount of amine curing agent (B))

[0159] The amount of the curing agent (B) relative to the total amount of the curing agent may be 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, or 80% by weight or more, preferably 77% by weight or more, and more preferably 92% by weight or more. In addition, the total amount of the curing agent relative to the total amount of the curing agent may be 100% by weight or less, 95% by weight or less, 85% by weight or less, 75% by weight or less, 65% by weight or less, or 55% by weight or less.

[0160] (Total amount of other additives)

[0161] The total amount of other additives can be appropriately selected according to each component. For example, the amount of other additives can be 0.01% by weight or more, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, or 0.8% by weight or more relative to the composition. In addition, the total amount of other additives can be 5% by weight or less, 4.5% by weight or less, 3.5% by weight or less, 3% by weight or less, 2.5% by weight or less, or 2% by weight or less relative to the composition.

[0162] <Method for preparing curable composition>

[0163] The curable composition may be prepared by any method as long as the various components can be uniformly dispersed and mixed. The composition may be prepared by kneading the components using a mixer such as a planetary mixer. Degassing may be performed as necessary during preparation.

[0164] The curable composition may be a one-component type or a multi-component type (eg, a two-component type), and is preferably a one-component type from the viewpoint of workability and preferably a multi-component type from the viewpoint of storage stability.

[0165] <Cured product>

[0166] The curable composition is cured by heating to form a cured product. The heating temperature can be 50 to 250°C, for example, 100°C to 175°C. The heating time is usually within 120 minutes, for example, within 60 minutes, preferably within 30 minutes, more preferably within 15 minutes, and further preferably within 10 minutes. When a curable composition is used as an underfill material, the curing temperature is a temperature set in consideration of the heat resistance of the electronic component, and is usually 50 to 200°C, for example, 80°C to 150°C.

[0167] The glass transition temperature of the cured product may be 128° C. or higher, 133° C. or higher, 138° C. or higher, 143° C. or higher, or 148° C. or higher. In addition, the glass transition temperature of the cured product may be 250° C. or lower, 200° C. or lower, or 175° C. or lower. By increasing the glass transition temperature of the cured product, the heat resistance can be improved.

[0168] As examples of bonds generated by curing, there are ether bonds, ester bonds or tertiary amino bonds. The ratio of the generated ether bonds can be 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more relative to 100 mol% of the generated bonds. The ratio of the generated ester bonds can be 20 mol% or less, 15 mol% or less, 10 mol% or less, or 7 mol% or more relative to 100 mol% of the generated bonds, preferably 12 mol% or less, and more preferably 8 mol% or less. The ratio of the generated tertiary amino bonds can be 12 mol% or less, 9 mol% or less, 6 mol% or less, or 3.5 mol% or more relative to 100 mol% of the generated bonds, preferably 7.5 mol% or less, and more preferably 2.5 mol% or less. The identification of the generated bonds can be carried out by using various spectroscopic methods such as NMR and IR.

[0169] The linear expansion coefficient of the cured product may be 31 ppm or less, 29 ppm or less, 25 ppm or less, or 23 ppm or less, preferably 30 ppm or less, more preferably 29 ppm or less, and further preferably 27 ppm or less. By making the linear expansion coefficient of the cured product low, the occurrence of defects in electronic components can be reduced.

[0170] <Application of curable composition>

[0171] The curable composition of the present invention is useful when permeability and low linear expansion coefficient are required. The curable composition of the present invention can be used in various applications such as adhesives or filling materials, and can be preferably used as a bottom filling material, particularly a bottom filling material for electronic component devices. In the electronic component device, the electronic component and the substrate are connected using the bottom filling material of the present invention or its cured product. The bottom filling material formed by the curable composition of the present invention is filled in the gap between the electronic component and the substrate, and then heated at a specified temperature for a specified time, so that an electronic component device formed by the electronic component and the substrate being joined using the cured product of the bottom filling material can be obtained.

[0172] [Example]

[0173] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. It should be noted that parts and % are by weight unless otherwise specified.

[0174] [Test method]

[0175] The test method and evaluation criteria are as follows.

[0176] (Particle size distribution)

[0177] The particle size distribution of inorganic particles (silicon dioxide) was measured by a wet method using a laser diffraction / scattering particle distribution measuring device (Partica LA-950V2 manufactured by Horiba, Ltd.). Methanol was used as a dispersion medium. In the case where the particle size distribution is broad and small particles are hidden in large-diameter particles and cannot be detected, the classified particles can be measured separately and the results of the two can be combined.

[0178] (Permeability)

[0179] Two glass slides were slightly offset and bonded to form a gap of 100 μm. A predetermined amount of curable composition (underfill material) was applied to the edge of the gap, and the temperature was raised from 25°C to 140°C over 10 minutes at 12.5°C / min, and the penetration distance after 10 minutes was measured.

[0180] (Storage stability)

[0181] 10 cc of the curable composition was placed in a vial, sealed and left to stand at 40°C, and the viscosity was measured after 96 hours. The viscosity was measured using a cone-plate viscometer (Brookfield HBDV-II+Pro) at a temperature of 25°C and a shear rate of 1 second. -1 Measure the viscosity under the conditions and find out how many times the viscosity increases.

[0182] (Curing property)

[0183] The curability of the bottom filler was calculated from the calorific value before and after curing using a DSC (differential scanning calorimeter, Q-2000 manufactured by TA Instruments Japan). The area enclosed by the heat curve and the baseline when the bottom filler was heated from 25°C to 200°C at a rate of 10°C / min was taken as the calorific value. The curability (%) was calculated using the following formula.

[0184] Curability (%) = ((calorific value before curing) - (calorific value after curing at 150°C for 3 minutes)) / (calorific value before curing) × 100

[0185] (Glass transition temperature and linear expansion coefficient)

[0186] The bottom filler was heated at 150°C for 3 minutes to obtain a cured product. The cured product was heated from -40°C to 250°C at a rate of 5°C / min using a TMA (thermomechanical analyzer, TMA7100 manufactured by Hitachi High-Tech Science Corporation), and the linear expansion coefficient was determined from the gradient of a straight line from 30°C to 80°C. The glass transition temperature (Tg) was calculated from the intersection of two tangent lines of the obtained TMA curve.

[0187] (Insulation)

[0188] After applying the bottom filler with a thickness of 200 μm on a JIS2 comb-shaped substrate, the test piece was cured at 150°C for 3 minutes. The test piece was placed in a constant temperature bath at 85°C and 90% RH, and a voltage of 32V was applied to each electrode to measure the resistance value after 1000 hours. For the measurement of insulation, a digital ultra-high resistance meter (R8340A manufactured by ADVANTEST) was used to obtain the resistance value after applying 100V for 1 minute.

[0189] (Temperature cycle test)

[0190] The bottom filler was applied between the semiconductor element (size: 2×2mm) of the SON (Small Outline No Lead) mounting substrate and the substrate, and after being infiltrated, it was heated and cured at 150°C for 3 minutes to obtain a test piece. After the test piece was exposed to a cold and hot shock environment of -30°C to 105°C (30 minutes each) / 3000 cycles, the state of the solder crack was observed using an electron microscope. Regarding the degree of solder crack progression, the complete fracture was taken as 100%, and the length ratio of the generated crack was calculated according to the following formula.

[0191] Crack extension (%) = (crack length / total crack length at complete fracture) × 100

[0192] [Examples 1 to 7, Comparative Examples 1 to 8]

[0193] The raw materials were mixed in a planetary mixer according to the composition (parts by weight) shown in Table 1 to obtain a curable composition. The above test was carried out using the obtained curable composition. The results are shown in Table 2.

[0194] Specifically, the raw materials shown in Table 1 are as follows:

[0195] Epoxy resin (a1): HP-4032D manufactured by DIC Corporation

[0196] Epoxy resin (a2-1): JER630 manufactured by Mitsubishi Chemical Corporation

[0197] Epoxy resin (a2-2): JER604 manufactured by Mitsubishi Chemical Corporation

[0198] Epoxy resin (a'1): JER828 manufactured by Mitsubishi Chemical Corporation

[0199] Epoxy resin (a'2): ED-505 manufactured by ADEKA

[0200] Curing agent (b): 2MZA-PW manufactured by Shikoku Chemical Co., Ltd., melting point: 248-258°C

[0201] Curing agent (b'1): C17Z manufactured by Shikoku Chemical Co., Ltd., melting point: 87-94°C

[0202] Curing agent (b'2): Dicyandiamide manufactured by Mitsubishi Chemical Corporation

[0203] Additive 1: Epoxysilane Shin-Etsu Chemical KBM403

[0204] Additive 2: Silicone oil Shin-Etsu Chemical KF-615A

[0205] Inorganic particles (cl): NIPPON STEEL Chemical & Material Co., Ltd. SC70-2

[0206] Inorganic particles (cs): NIPPON STEEL Chemical & Material Co., Ltd. SP60

[0207] Colorant: MA100 manufactured by Mitsubishi Chemical Corporation

[0208] [Table 1]

[0209]

[0210] [Table 2]

[0211]

[0212] Industrial Applicability

[0213] The curable composition of the present invention can be used in various applications such as adhesives and fillers, and can be preferably used as an underfill material, particularly an underfill material for production of electronic components.

Claims

1. A cured product, which is a cured product of a curable composition, wherein the curable composition comprises: Naphthalene type epoxy resin (A1), Glycidylamine type epoxy resin (A2), Amine curing agent (B) with a melting point of 100°C or above and Inorganic filler material (C), The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents, The amount of the naphthalene epoxy resin (A1) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the glycidylamine epoxy resin (A2) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the inorganic filler (C) is 60% by weight or more relative to the composition, The total amount of the curing agent is 0.2% by weight or more and 5.0% by weight or less based on the composition, The number of nitrogen atoms in the amine curing agent (B) molecule is 3 or more, and / or the nitrogen content of the amine curing agent (B) is 20 wt % or more, and the nitrogen content is 14×the number of nitrogen atoms in the amine curing agent (B) molecule / the molecular weight of the amine curing agent (B)×100 wt %.

2. The cured product according to claim 1, wherein The amine curing agent (B) is a curing agent containing a triazine skeleton.

3. The cured product according to claim 1 or 2, wherein The amount of the naphthalene-type epoxy resin (A1) is 35% by weight or more based on the amount of organic matter in the composition.

4. The cured product according to claim 1 or 2, wherein The glycidylamine epoxy resin (A2) is aromatic, and its monomer structure has only one nitrogen atom.

5. The cured product according to claim 1 or 2, wherein The inorganic filler (C) includes spherical inorganic particles.

6. The cured product according to claim 5, wherein The spherical inorganic particles include Spherical inorganic particles (Cs) with a center particle size in the range of 0.5 to 5 μm, and Spherical inorganic particles (Cl) with a center particle size in the range of 5 to 20 μm, The difference between the center particle diameter of the spherical inorganic particles (Cs) and the center particle diameter of the spherical inorganic particles (Cl) is at least 1 μm.

7. The cured product according to claim 5, wherein In the volume-based particle size distribution measurement of the spherical inorganic particles, in a particle abundance ratio diagram plotted with particle diameter as the horizontal axis and particle abundance ratio as the vertical axis, there are at least two peaks or shoulders in the particle diameter range of 0.5 to 20 μm.

8. The cured product of the curable composition according to claim 1 or 2, wherein The linear expansion coefficient is 31 ppm or less.

9. A cured product of the curable composition according to claim 1 or 2, wherein The linear expansion coefficient is 27 ppm or less.

10. A cured product of an underfill material, the underfill material comprising: Naphthalene type epoxy resin (A1), Glycidylamine type epoxy resin (A2), Amine curing agent (B) having a melting point of 100°C or more and Inorganic filler material (C), The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents, The amount of the naphthalene epoxy resin (A1) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the glycidylamine epoxy resin (A2) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the inorganic filler (C) is 60% by weight or more relative to the composition, The total amount of the curing agent is 0.2% by weight or more and 5.0% by weight or less based on the composition, The number of nitrogen atoms in the amine curing agent (B) molecule is 3 or more, and / or the nitrogen content of the amine curing agent (B) is 20 wt % or more, and the nitrogen content is 14×the number of nitrogen atoms in the amine curing agent (B) molecule / the molecular weight of the amine curing agent (B)×100 wt %.

11. The cured product of the underfill material according to claim 10, wherein: The linear expansion coefficient is 31 ppm or less.

12. The cured product of the underfill material according to claim 10, wherein: The linear expansion coefficient is 27 ppm or less. 13 . An electronic component device, wherein an electronic component and a substrate are connected using the cured product of the underfill material according to claim 10 . 14 . A method for manufacturing an electronic component device, comprising the step of forming a cured product of the underfill material according to claim 10 in a gap between an electronic component and a substrate.

15. A curable composition, wherein: Include: Naphthalene type epoxy resin (A1), Glycidylamine type epoxy resin (A2), Amine curing agent (B) with a melting point of 100°C or above and Inorganic filler material (C), The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents, The amount of the naphthalene epoxy resin (A1) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the glycidylamine epoxy resin (A2) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the inorganic filler (C) is 60% by weight or more relative to the composition, The total amount of the curing agent is 0.2% by weight or more and 5.0% by weight or less based on the composition, The number of nitrogen atoms in the amine curing agent (B) molecule is 3 or more, and / or the nitrogen content of the amine curing agent (B) is 20 wt % or more, and the nitrogen content is 14×the number of nitrogen atoms in the amine curing agent (B) molecule / the molecular weight of the amine curing agent (B)×100 wt %.

16. The curable composition according to claim 15, wherein The amine curing agent (B) is a curing agent containing a triazine skeleton.

17. The curable composition according to claim 15 or 16, wherein The amount of the naphthalene-type epoxy resin (A1) is 35% by weight or more based on the amount of organic matter in the composition.

18. The curable composition according to claim 15 or 16, wherein The glycidylamine epoxy resin (A2) is aromatic, and its monomer structure has only one nitrogen atom.

19. The curable composition according to claim 15 or 16, wherein The inorganic filler (C) includes spherical inorganic particles.

20. The curable composition according to claim 19, wherein The spherical inorganic particles include Spherical inorganic particles (Cs) with a center particle size in the range of 0.5 to 5 μm, and Spherical inorganic particles (Cl) with a center particle size in the range of 5 to 20 μm, The difference between the center particle diameter of the spherical inorganic particles (Cs) and the center particle diameter of the spherical inorganic particles (Cl) is at least 1 μm.

21. The curable composition according to claim 19, wherein In the volume-based particle size distribution measurement of the spherical inorganic particles, in a particle abundance ratio diagram plotted with particle diameter as the horizontal axis and particle abundance ratio as the vertical axis, there are at least two peaks or shoulders in the particle diameter range of 0.5 to 20 μm.

22. A bottom filling material, wherein: Include: Naphthalene type epoxy resin (A1), Glycidylamine type epoxy resin (A2), Amine curing agent (B) having a melting point of 100°C or more and Inorganic filler material (C), The amine curing agent (B) is at least one selected from the group consisting of imidazole curing agents and imidazoline curing agents, The amount of the naphthalene epoxy resin (A1) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the glycidylamine epoxy resin (A2) is 20% by weight or more relative to the amount of organic matter in the composition. The amount of the inorganic filler (C) is 60% by weight or more relative to the composition, The total amount of the curing agent is 0.2% by weight or more and 5.0% by weight or less based on the composition, The number of nitrogen atoms in the amine curing agent (B) molecule is 3 or more, and / or the nitrogen content of the amine curing agent (B) is 20 wt % or more, and the nitrogen content is 14×the number of nitrogen atoms in the amine curing agent (B) molecule / the molecular weight of the amine curing agent (B)×100 wt %.

23. An electronic component device, wherein an electronic component and a substrate are connected using the underfill material according to claim 22. 24 . A method for manufacturing an electronic component device, comprising the step of filling the underfill material according to claim 22 into a gap between an electronic component and a substrate.

Citation Information

Patent Citations

  • Imidazole compound, epoxy resin curing agent and epoxy resin composition

    JP2015140394A

  • Production method of resin composition for encapsulation and method for manufacturing electronic device

    JP2019006972A

  • Underfill material, semiconductor package and method for producing semiconductor package

    JP2019011409A

  • Antifouling coating film with low frictional resistance with water or seawater

    WO2014142035A1

  • Method for preparing copper-clad laminate by using polyphenylene oxide resin composition

    CN108263068A